ANALISIS PEMAHAMAN KONSEP MAHASISWA PADA MATERI ASAM BASA MENGGUNAKAN INSTRUMEN ABCD TEST - Tiwi Nur Astuti; Achmad Ridwan; Ella Fitriani; Sarina Hanifah; Haya Satirah Hanin; Muhammad Fajar Irzha Farindra (Chemistry Education Practice, 2026)
This study aims to analyze the level of understanding of acid-base concepts among prospective chemistry teachers. Understanding acid-base concepts is an important foundation in chemistry education. Using a mixed-methods explanatory design, the acid-base concept diagnostic (ABCD) test was administered to assess understanding and identify misconceptions regarding fundamental acid-base concepts. The results of the study indicate that the lowest level of conceptual understanding was observed for question 9 (11.94%; 16 out of 134 students answered correctly). In contrast, the highest level of conceptual understanding was observed in question 25 (82.84%, or 111 out of 134 students answered correctly). The average total percentage of students who answered the questions correctly was 57.34%, placing it in the moderate category. This is supported by qualitative analysis results indicating that students still experience misconceptions, particularly in determining acid-base strength and pH, and in identifying conjugate acids and bases. Integration of diagnostic assessment into chemistry learning strategies is necessary to strengthen the conceptual competence of prospective teachers.